Mammary Analogue Secretory Carcinoma of Parotid gland: literature review and experience of a dedicated cancer institution in Pakistan - Hamza Shahid; Rahim Dhanani; Muhammad Faisal; Abdul Rehman; Arif Jamshed; Raza Hussain (Journal of the Pakistan Medical Association, 2022)
Mammary Analogue Secretory Carcinoma (MASC) is a rare pathology of the salivary gland, most commonly involving the parotid gland. The objective of this study was to identify the characteristic features of MASC and its treatment outcomes. A retrospective review of 12 patients with histological diagnosis of MASC, who were managed between 2010 to 2019, was carried out at the Shaukat Khanum Memorial Cancer Hospital & Research Centre, Lahore. Their mean age was 34 (±16) years. There were 9 (75%) male and 3 (25%) female patients. Painless slow growing swelling was the most common presenting symptom. All the patients had undergone surgical excision with or without neck dissection, followed by adjuvant treatment. Of these, six patients had T2 tumours, while four had cervical lymph node metastasis. The mean follow-up period was 23 (±21) months. Local recurrence was seen in one patient. MASC is considered a low-grade tumour with good prognosis which can be treated with curative intent of surgery followed by radiotherapy effectively. Keywords: Mammary analogue secretory carcinoma, Parotid gland, Salivary tumour.